2017
DOI: 10.17235/reed.2017.4575/2016
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of liver changes in ZSF1 rats, an animal model of metabolic syndrome

Abstract: A, Pimentel-Nunes P. Characterization of liver changes in ZSF1 rats, an animal model of metabolic syndrome. Rev Esp Enferm Dig 2017;109(7): 491-497. DOI: 10.17235/reed.2017491-497. DOI: 10.17235/reed. .4575/2016 Received: 26-08-201626-08- Accepted: 25-02-2017 Correspondence: Marta Borges-Canha. Department of Physiology and Cardiothoracic Surgery. Faculty of Medicine. University of Porto. Alameda Prof. Hernâni Monteiro. 4200-319 Porto, Portugal e-mail: marta.canha@gmail.com ABSTRACT Background:The non-alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…For each bacterial group in the PCA biplot diagram (Figure D), the length of the line is directly proportional to contribution and the direction of the line indicates the time point that bacterial group contributed to. At the level of family, GTL significantly increased the SCFA‐producing Lachinospiraceae and Ruminococcaceae , elevated Erysipelotrichaceae and Bifidobacteriaceae and Coriobacteriaceae and decreased Prevotellaceae (Figure I–O) . Notably, the GTL effect on Ruminococcaceae and Bifidobacteriaceae were irreversible (Figure K,M).…”
Section: Resultsmentioning
confidence: 97%
“…For each bacterial group in the PCA biplot diagram (Figure D), the length of the line is directly proportional to contribution and the direction of the line indicates the time point that bacterial group contributed to. At the level of family, GTL significantly increased the SCFA‐producing Lachinospiraceae and Ruminococcaceae , elevated Erysipelotrichaceae and Bifidobacteriaceae and Coriobacteriaceae and decreased Prevotellaceae (Figure I–O) . Notably, the GTL effect on Ruminococcaceae and Bifidobacteriaceae were irreversible (Figure K,M).…”
Section: Resultsmentioning
confidence: 97%
“…Although the obese ZSF1 rat is not a model of liver disease per se, this model is known to develop steatosis with age, typically beginning around 20-24 weeks (Zambad et al, 2011;Borges Canha et al, 2017). As a model of diabetes, disease progression may reflect that seen in humans with type 2 diabetes who develop increasingly severe comorbidities.…”
Section: Olinciguat Treatment Affected Cardiometabolic Risk Factors Amentioning
confidence: 99%
“…This suggests that the general bifidogenic effect observed upon inulin consumption can also be observed upon the consumption of inulin incorporated into a processed meat product. Earlier findings have revealed that bifidobacteria reduced azoxymethane‐induced colon carcinogenesis in rats and studies have indicated associations between colorectal cancer and diminished levels of bifidobacteria in the gut . At the genus level, an increased relative abundance of an unclassified Lachnospiraceae was found after the consumption of inulin‐enriched sausages compared to control sausages.…”
Section: Discussionmentioning
confidence: 91%